2010
DOI: 10.1186/1755-7682-3-37
|View full text |Cite
|
Sign up to set email alerts
|

Treatment results and prognostic factors of pediatric neuroblastoma: a retrospective study

Abstract: BackgroundWe conducted a retrospective analysis to investigate treatment results and prognostic factors of pediatric neuroblastoma patients.MethodsThis retrospective study was carried out analyzing the medical records of patients with the pathological diagnosis of neuroblastoma seen at South Egypt Cancer Institute, Assiut University during the period from January 2001 and January 2010. After induction chemotherapy, response according to international neuoblastoma response criteria was assessed. Radiotherapy to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
1
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 26 publications
(41 reference statements)
0
9
1
1
Order By: Relevance
“…Amplification of the MYCN oncogene, first described in NB patient in 1983 was one of the first genes shown to be of prognostic value in pediatric oncology and MYCN-amplification maintains its relevance as a marker of high-risk disease for patients with loco regional NB. Besides this, age more than one year, disseminated disease, 1p deletion, 17q25 duplication, di-, or tetraploid DNA content of tumor cells, elevated blood level of LDH and NSE are also unfavorable prognostic factors [1,2,[7][8][9].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Amplification of the MYCN oncogene, first described in NB patient in 1983 was one of the first genes shown to be of prognostic value in pediatric oncology and MYCN-amplification maintains its relevance as a marker of high-risk disease for patients with loco regional NB. Besides this, age more than one year, disseminated disease, 1p deletion, 17q25 duplication, di-, or tetraploid DNA content of tumor cells, elevated blood level of LDH and NSE are also unfavorable prognostic factors [1,2,[7][8][9].…”
Section: Discussionmentioning
confidence: 99%
“…While in the staging of the disease the mIBG (metaiodobenzylguanidine) scintigraphy is available [1,8,9].…”
Section: Discussionmentioning
confidence: 99%
“…На-ряду с параметрами клинического характера (возраст пациента [22], распространение и локализация опухо-ли [7,23]) многообещающими оказались гистологи-ческие (гистопатологическая классификация по си стеме Н. Shimada [20], количество клеток с митозом [24] и апоптозом), молекулярно-биохимические (плоид-ность [25, 26]) и генетические (хромосомные аберра-ции, статус гена MYCN, делеция локусов 1р36 и 11q, увеличение длинного плеча хромосомы 17 и др.) ха-рактеристики опухолевых клеток [17,[27][28][29].…”
Section: обзорные статьиunclassified
“…Radiotherapy is an important tool for the control of pain and local neoplastic progression. Several studies have demonstrated its efficacy in stabilizing the progression of pain and in maintaining the ability of the patient to walk, which are considered import goals of treatment [3-6]. …”
Section: Introductionmentioning
confidence: 99%